Triassic High-Mg Diorites and Granitoids in the NE Pamir Reveal Tectonic Evolution of the Paleo-Tethys Ocean - Xiao-Qiang Liu; Chuan-Lin Zhang; Masumeh Sargazi; Hua-Dong Ma; Aerken Xiaili; Xu-Kun Qian; Zhi-Hao Song (Lithosphere)
The Western Kunlun-Pamir Orogen (WKPO) in the northwestern Tibetan Plateau holds crucial information on the Tethyan evolution. Until now, the subduction polarity and the assemblage processes of the Northern, Central, and Southern Pamir during the Paleo-Tethys period are still intensely debated among geologists. In this study, we reported field observation, petrography, zircon U-Pb ages, whole-rock geochemistry, and Nd-Hf isotopes of the Triassic high-Mg diorites and coeval granitoids from the Muji area in the northeastern Pamir, in order to elucidate their petrogenesis and to decipher the Paleo-Tethys tectonic evolution. Zircon LA-MC-ICPMS U-Pb dating indicates that these granitoids were emplaced between 225 and 213 Ma. The occurrence of clinopyroxene and the moderate to high SiO2 (52.71%–58.51%) and MgO contents (3.31%–6.05%) and Mg# values (47–62), along with moderate to high Y (12.6, 22.6 ppm), Yb (1.40, 2.19 ppm), Th (2.54, 11.0 ppm), and Th/U ratios (2.5, 4.4), (La/Sm)N(2.5, 4.2), resemble those sanukitic high-Mg andesites. Conversely, the granitoids display higher SiO2(63.06%–72.13%), and lower Mg# (30–56). Isotopically, both the gabbro diorites and granitoids exhibit enriched whole-rock Sm-Nd isotopes with εNd(t) values ranging from −5.03 to −4.24 and from −8.35 to −4.17, respectively. In addition, the granitoids have a large range of zircon εHf(t) values ranging from −9.8 to 5.8. The absence of negative Zr-Hf anomalies in both gabbro diorites and granitoids reveals a specific dynamic background of a hot subduction geothermal gradient. Our data suggest that the gabbro diorites originated from partial melting of a lithospheric mantle modified by subducted sediment-derived melt, whereas the granitoids were derived from mixing of subduction-modified mantle-derived mafic melts with varying proportions of ancient crustal-derived felsic components. Integrating with the Early Mesozoic geology of the WKPO, we suggest that the final closure of the Paleo-Tethys Ocean in the northeastern Pamir was most likely in early Jurassic, which led to the embryonic architecture of the Pamir.